EXPANSION OF TECHNOLOGICAL CAPABILITIES OF ROLLING STAMPING BY INDUCTION SURFACE HEATING OF COMPLEX-PROFILE BLANKS - SHTUTS, ANDRII; YANOVYCH, VITALII; YAROPUD, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers an innovative approach to increasing the efficiency of the rolling stamping process (SHO) of complex-profile blanks by using induction surface heating. The proposed technique provides increased plasticity of materials, reduced contact stresses and increased stability of blanks during deformation, which is especially important when processing materials with low plasticity or complex geometry. The technique consists in local heating of only those areas of the blank that are subject to direct deformation, which allows achieving a uniform temperature distribution in the material. This approach minimizes energy consumption and provides high control over the heating process. Local heating helps to increase the plasticity of the material by 30-50%, which significantly improves the processing capabilities of complex-profile workpieces. In addition, contact stresses are reduced, which ensures the stability of the dimensional parameters of finished products and increases the tooling resource by 20-30%, reducing the costs of its maintenance and replacement. A special device for SH of flange parts has been developed, taking into account the possibility of induction heating, which allows optimizing the processing process at all stages of production. The modeling of the technological parameters of the process has shown that the use of induction heating at a temperature of 1150-1200°C provides the necessary conditions for plastic deformation of the material even in complex-profile workpieces. This temperature regime allows avoiding premature material failure, reducing the number of defects and scrap in production. The results of the research confirm that the combination of SH with induction heating significantly expands the technological capabilities of the process. This contributes to improving the quality of finished products, the stability of dimensional and geometric parameters, and also reduces the cost of production by reducing the cost of materials and equipment. In addition, the proposed technology has a positive effect on the stability of the production process, reducing the dependence of the final result on changes in technological parameters. The proposed technology has significant potential for implementation in various industries, such as mechanical engineering, aviation, automotive and energy industries. It contributes to increasing the economic efficiency of production by optimizing technological processes, increasing equipment productivity and ensuring stable product quality even during mass production.